2016
DOI: 10.1136/bcr-2016-217183
|View full text |Cite
|
Sign up to set email alerts
|

Sequential adjuvant chemoradiotherapy-induced diffuse alveolar haemorrhage in a patient with breast cancer successfully treated with corticosteroid plus recombinant human soluble thrombomodulin

Abstract: The effective treatment for corticosteroid (CS)-refractory sequential chemoradiotherapy (CRT)-induced lung injury has not been established. We report a case of sequential CRT-induced diffuse alveolar haemorrhage (DAH) successfully treated with CS therapy plus recombinant human soluble thrombomodulin (rhTM). A 69-year-old woman was treated with sequential adjuvant CRT for early-stage breast cancer. After sequential CRT, she suffered from progressive dyspnoea. Chest CT scan showed consolidations in the irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The development of DAH caused by sequential adjuvant chemoradiotherapy for BC was also described in a female patient with BC (an adenocarcinoma of the left breast, pT1cN0M0) originally treated with conserving surgery and subsequently with adjuvant radiotherapy and chemotherapy. The symptoms related with the evolving DAH appeared 9 days after the third administration of docetaxel and cyclophosphamide (3 months after the final irradiation) [5].…”
Section: Discussionmentioning
confidence: 99%
“…The development of DAH caused by sequential adjuvant chemoradiotherapy for BC was also described in a female patient with BC (an adenocarcinoma of the left breast, pT1cN0M0) originally treated with conserving surgery and subsequently with adjuvant radiotherapy and chemotherapy. The symptoms related with the evolving DAH appeared 9 days after the third administration of docetaxel and cyclophosphamide (3 months after the final irradiation) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Ougon is suspected to cause JHM-induced pneumonitis in many cases, and we found that 27 JHMs produced by Tsumura contained ougon . The results of a DLST using peripheral blood were positive for ougon , although the sensitivity of the DLST was not enough to detect drug-induced pneumonitis (9). In addition, the activity of each crude drug may change after being mixed with other drugs.…”
Section: Discussionmentioning
confidence: 99%